Perancangan Sistem Presensi Karyawan Berbasis Web Dengan Integrasi GPS Menggunakan Laravel dan Metode RAD (Rapid Application Development) pada PT. Kolling Advertising - Muhammad Ashori Fahmi; Muhammad Bintang Pamungkas; Tri Wahyudi; Joko Priambodo (CV. Shofanah Media Berkah, 2025)
This research aims to design and develop a web-based employee attendance system integrated with GPS using the Laravel framework and the Rapid Application Development (RAD) method for PT. Kolling Advertising. The system is created to address several issues found in manual attendance processes, such as data loss, slow recap processing, and potential fraud, including proxy attendance. The development process includes requirements analysis, interface design, implementation of core features (attendance, leave request, recapitulation, and leaderboard), GPS-based location validation, and Black Box testing. The results indicate that the system is capable of processing attendance data in real time, reducing data manipulation, and improving administrative efficiency. Therefore, the proposed system successfully enhances attendance monitoring and supports effective employee management within the company.